Heat dissipation substrate material primarily made from aluminum nitride

JP2026166486APending Publication Date: 2026-10-14NORITAKE MACHINE TECHNO CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025059449
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

Smart Images

  • Figure 2026166486000001_ABST
    Figure 2026166486000001_ABST
Patent Text Reader

Abstract

The present invention provides a heat dissipation substrate material mainly composed of aluminum nitride, and in particular, a heat dissipation substrate material that can improve the strength of such a heat dissipation substrate even when it is manufactured. [Solution] A granulated powder 10 is made by containing aluminum nitride powder and needle-shaped particles as raw materials, wherein the granulated powder 10 has needle-shaped portions 14, and the protruding length L of the needle-shaped portions 14 is 70 μm or less. When a heat dissipation substrate is made using such granulated powder 10, a heat dissipation substrate with good heat dissipation (thermal conductivity) and strength can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to granulated powder containing aluminum nitride as a main raw material.

Background Art

[0002] Semiconductors used for power control and the like, so-called power semiconductors, are widely used. In such power semiconductors, a ceramic heat dissipation substrate is attached to dissipate heat generated during operation. Among various ceramic materials, ceramics containing aluminum nitride (AlN) with excellent thermal conductivity are being studied.

[0003] Patent Document 1 describes that a green molded body is produced using granulated powder containing aluminum nitride powder, the green molded body is further fired to obtain a ceramic sintered body, and the ceramic sintered body thus obtained is interposed between a heat-generating component and a heat-dissipating component, or is used as a heat-dissipating sheet that replaces a heat-dissipating component.

Prior Art Documents

Patent Documents

[0004]

Patent Document 1

Summary of Invention

Problems to be Solved by the Invention

[0005] Meanwhile, aluminum nitride has a property of lower fracture toughness compared to other ceramic materials. Therefore, when a heat dissipation substrate is produced and used using such aluminum nitride, there is a possibility that cracks or fractures may occur after thermal cycles, and there is still room for improvement to address such problems.

[0006] On the other hand, it is conceivable to use aluminum nitride, one of the raw materials, in needle-shaped form in addition to granular powder form. However, simply using needle-shaped aluminum nitride, or mixing it with powdered aluminum nitride, may lead to the following problems: namely, the granulated powder containing needle-shaped aluminum nitride may come into contact with each other, causing the needle-shaped particles to intertwine and aggregate, potentially forming clumps.

[0007] If granulated powder containing such clumps is used, for example, in the green sheet obtained by molding the granulated powder, the needle-shaped particles may be unevenly distributed, resulting in insufficient strength and the possibility of crack propagation. Furthermore, if the clumps become large, they may exceed the thickness of the green sheet to be produced, making it impossible to achieve the desired thickness.

[0008] Based on the above circumstances, the inventors of this invention conducted various studies and found that by appropriately adding needle-shaped particles to aluminum nitride powder, it is possible to produce granulated powder with needle-shaped protrusions. Furthermore, they found that by making the length of the needle-shaped protrusions shorter than a predetermined length, it is possible to suppress the entanglement of these needle-shaped protrusions, which would result in the granulated powder forming large clumps. This invention is based on these findings.

[0009] The present invention has been made against the above circumstances, and its objective is to provide a heat dissipation substrate material mainly composed of aluminum nitride, and in particular, a heat dissipation substrate material that can improve the strength of such a heat dissipation substrate even when it is manufactured. [Means for solving the problem]

[0010] In other words, the gist of the first invention is a granulated powder characterized by (a) being made from aluminum nitride powder and needle-shaped particles as raw materials, (b) having needle-shaped protrusions, and (c) having a length of 70 μm or less of the needle-shaped protrusions.

[0011] Furthermore, the essence of the second invention is that, in the first invention, it is the front body of the green sheet for the heat dissipation substrate.

[0012] Furthermore, the gist of the third invention is that, in addition to the raw materials mentioned above, the first invention includes a water-soluble acrylic resin and a higher fatty acid as additives. [Effects of the Invention]

[0013] According to the granulated powder of the first invention, granulated material having needle-shaped protrusions with a length of 50 μm or less can be produced using needle-shaped particles as a raw material.

[0014] According to the granulated powder of the second invention, the needle-shaped particles in the granulated powder can improve the strength of the green sheet.

[0015] According to the granulated powder of the third invention described above, granulated powder can be suitably produced even when aluminum nitride, which undergoes hydrolysis upon reaction with an aqueous solvent, is used as a raw material. [Brief explanation of the drawing]

[0016] [Figure 1] This figure conceptually illustrates the shape of the granulated powder of the present invention. [Figure 2] This figure illustrates the granulated powder of the present invention and the process for manufacturing a heat dissipation substrate using the granulated powder. [Modes for carrying out the invention]

[0017] Preferred embodiments of the technology disclosed herein will be described below. Matters other than those specifically mentioned herein (e.g., the composition and properties of granulated powder and green molded articles) that are necessary for carrying out the present invention (e.g., methods for producing granulated powder, methods for molding green molded articles, etc.) can be carried out based on the technical content taught herein and the general technical common sense of those skilled in the art. The present invention can be carried out based on the content disclosed herein and the general technical common sense of the art. In this specification, the notation "X~Y (where X and Y are arbitrary values)" indicating a numerical range includes not only the meaning of "greater than or equal to X and less than or equal to Y," but also the meanings of "preferably greater than X" and "preferably less than Y."

[0018] [Granulated powder] Granulated powder (hereinafter also referred to as granulated powder) is obtained by processing aluminum nitride powder, which is used as a raw material, into granules for the purpose of improving the handling properties of aluminum nitride powder. Granulated powder can be used, for example, in the manufacture of green molded bodies and ceramic sintered bodies. In the technology disclosed herein, granulated powder essentially contains (A) aluminum nitride powder and (B) (B1) water-soluble acrylic resin and (B2) higher fatty acids as additives. Granulated powder may further contain (C) other optional components. Granulated powder can be suitably manufactured by the manufacturing method described later. Granulated powder may further contain moisture, for example, derived from the manufacturing method. The amount of moisture may be 0.1% by mass or more, 0.2% by mass or more, and 1.0% by mass or less, when the total amount of granulated powder is considered to be 100% by mass. The properties of granulated powder and each constituent component will be described in order below.

[0019] Figure 1 illustrates an example of the shape of the granulated powder 10 of this embodiment. The granulated powder 10 is composed of granular parts 12 and needle-shaped parts 14. The needle-shaped parts 14 are provided so as to penetrate the granular parts 12. The needle-shaped parts 14 correspond to the needle-shaped projections of the present invention.

[0020] The properties, such as shape and size, of the particles constituting the granular portion 12 are not particularly limited. The shape of the granulated powder is typically substantially spherical. However, it may be flaky (scale-like), plate-like, irregular, or the like. As used in the present specification, "substantially spherical" refers to a form that can be generally regarded as a sphere as a whole, and means that the average aspect ratio (major axis / minor axis ratio) based on an observation image with an electron microscope is approximately 1 to 2, for example 1 to 1.5.

[0021] Although not particularly limited, the average particle diameter of the granular portion 12 is preferably approximately 1 μm or more, for example 10 μm or more, 15 μm or more, 20 μm or more, or 30 μm or more, from the viewpoint of improving handleability and the like. In addition, the average particle diameter of the granular portion 12 is preferably approximately 200 μm or less, for example 150 μm or less, 100 μm or less, or 80 μm or less. As used in the present specification, the "average particle diameter" refers to the particle diameter (D50 particle diameter) corresponding to 50% cumulative from the fine particle side in the volume-based particle size distribution measured by particle size distribution measurement based on a laser diffraction / scattering method.

[0022] The acicular portion 14 is a portion having an elongated shape extending from the granular portion 12. The length of the elongated shape in the longitudinal direction is sufficiently long relative to the particle diameter of the granular portion 12, and the length of the elongated shape in the cross-sectional direction is sufficiently short relative to the particle diameter of the granular portion 12. The length of the acicular portion 14 protruding from the granular portion 12 is referred to as a protruding length L, and when a plurality of acicular portions 14 protrude from the granular portion 12, the longest protruding length L among them is referred to as the protruding length of the granulated powder 10.

[0023] (A1) Aluminum nitride powder The aluminum nitride powder is a main component of the ceramic sintered body after firing. The aluminum nitride powder is a powder mainly composed of aluminum nitride (AlN) particles. Although the representative composition is described in parentheses above, it is not intended to be strictly limited to those having the exact composition. For example, other elements may be added for the purpose of obtaining desired properties, and various compounds, metals and the like may be composited.

[0024] The properties of the particles constituting the aluminum nitride powder, such as shape and size, are not particularly limited. The shape of the aluminum nitride powder may be, for example, approximately spherical, flake-like, fibrous, or irregularly shaped. Furthermore, the average particle diameter of the aluminum nitride powder is preferably 0.01 μm or larger, for example, 0.1 μm or larger, 0.5 μm or larger, or 1 μm or larger, from the viewpoint of suppressing hydrolysis and improving handling properties. Furthermore, from the viewpoint of improving moldability, it is preferable that the particle diameter be approximately 50 μm or smaller, for example, 30 μm or smaller, and even 15 μm or smaller.

[0025] (A2) Acicular particles The needle-shaped particles are crystalline particles of aluminum nitride, similar to the aluminum nitride powder. The needle-shaped particles have a plate-like or needle-like shape, and are elongated crystalline particles with a length of, for example, 10 to 1000 micrometers (μm). The needle-shaped particles have an elongated shape, and their size in the longitudinal direction is much larger than their size in the cross-sectional direction perpendicular to the longitudinal direction.

[0026] While not particularly limited, when the total mass of the granulated powder is considered to be 100%, the proportion of aluminum nitride powder and needle-shaped particles is generally 70% or more by mass, typically 80% or more by mass, for example 85% or more by mass, or 90% or more by mass, and generally 99% or less by mass, typically 98% or less by mass, for example 95% or less by mass. When the above proportion is above a predetermined value, the aluminum nitride particles come into contact with each other more easily in the ceramic sintered body, improving density and thermal conductivity. Furthermore, when the above proportion is below a predetermined value, hydrolysis can be more effectively suppressed. In addition, moldability and handling properties are improved, and a granulated powder with high integrity and resistance to collapse can be stably produced.

[0027] (B) Additives The additive is a component that functions as a binder to maintain the integrity of the granulated powder by binding at least the aluminum nitride particles together, and also functions as a coating agent to suppress the hydrolysis of the aluminum nitride powder. In the art disclosed herein, the additive consists of (B1) a water-soluble acrylic resin and (B2) a higher fatty acid. (B1) the water-soluble acrylic resin and (B2) the higher fatty acid are mixed in a predetermined ratio. The additive typically adheres to at least a portion of the surface of the aluminum nitride particles, and preferably covers the entire surface.

[0028] (B1) Water-soluble acrylic resin In this specification, "water-soluble acrylic resin" means an acrylic resin soluble in an aqueous solvent, and an acrylic resin (emulsion) that can be homogeneously dispersed in an aqueous solvent. In this specification, "soluble" means that 1 g or more dissolves in 100 mL of an aqueous solvent at 25°C. The aqueous solvent is typically water, but may also contain a non-aqueous solvent that can be homogeneously mixed with water (e.g., lower alcohols or lower ketones). In this case, it is preferable that 95% or more by volume of the aqueous solvent is water. Advantages of water-soluble acrylic resins include their high adhesiveness, which allows for strong adhesion between aluminum nitride particles with relatively small amounts of additive, and their high flammability, resulting in less firing residue regardless of the firing atmosphere.

[0029] Water-soluble acrylic resins encompass all polymers and their derivatives that contain at least alkyl (meth)acrylate as a constituent monomer component. Examples of water-soluble acrylic resins include homopolymers containing 100% by mass of alkyl (meth)acrylate as a constituent monomer component, and copolymers (including graft copolymers) in which alkyl (meth)acrylate is the main monomer (a component accounting for more than 50% by mass of the total monomer) and which contains copolymerizable sub-monomers to the main monomer. In this specification, "(meth)acrylate" means acrylate and methacrylate, and "(meth)acrylic" means acrylic and methacrylic.

[0030] As the alkyl (meth)acrylate, for example, a compound represented by the general formula: CH2=C(R1)COOR2 can be suitably used. Here, R1 represents a hydrogen atom or a methyl group. R2 represents a chain alkyl group having 1 to 20 carbon atoms. For R2, an alkyl (meth)acrylate with a chain alkyl group having 1 to 14 carbon atoms is preferred, and an alkyl (meth)acrylate with a chain alkyl group having 1 to 12 carbon atoms is more preferred.

[0031] As secondary monomers, for example, monomer components containing various functional groups can be used, which have the function of introducing crosslinking points into water-soluble acrylic resins or adjusting the binding properties of water-soluble acrylic resins. Functional groups contained in the monomer components may include, for example, carboxyl groups, hydroxyl groups, amide groups, amino groups, epoxy groups, etc. The ratio of secondary monomers to the total amount of main monomers and secondary monomers can be, for example, 1 to 10% by mass. Specific examples of secondary monomers include 2-hydroxyethyl (meth)acrylate, dimethylaminoethyl (meth)acrylate, vinyl alcohol monomers, copolymerizable monomers into which dialkylamino groups, carboxyl groups, alkoxycarbonyl groups, etc. Examples of copolymers include poly(meth)acrylic acid, vinyl chloride / acrylic graft copolymer resins, vinyl acetal / acrylic graft copolymer resins, etc.

[0032] It is preferable that the water-soluble acrylic resin does not decompose by heat treatment (e.g., heat treatment at 100-200°C) to dry the granulated powder. It is also preferable that the water-soluble acrylic resin burns away by debinding treatment (e.g., heat treatment at 200-600°C) or firing treatment exceeding 600°C (e.g., heat treatment at 1000-2500°C). It is preferable that the decomposition temperature of the water-soluble acrylic resin is the heating temperature of the debinding treatment or firing treatment described above, regardless of the firing atmosphere.

[0033] The weight-average molecular weight of water-soluble acrylic resin is generally 5,000 or more, for example, 10,000 or more, from the viewpoint of improving tackiness. The weight-average molecular weight may generally be 1,000,000 or less, typically 500,000 or less, for example, 300,000 or less, 200,000 or less, or 100,000 or less. In this specification, "weight-average molecular weight" refers to the average molecular weight on a weight basis, measured by gel permeation chromatography (GPC) and converted using a standard polystyrene calibration curve.

[0034] The glass transition temperature of water-soluble acrylic resin is generally preferably 30°C or lower, for example, 25°C or lower, 20°C or lower, 10°C or lower, 0°C or lower, -10°C or lower, or -20°C or lower, from the viewpoint of improving the moldability and integrity of the granulated powder. The glass transition temperature may also be generally -200°C or higher, for example, -100°C or higher, -80°C or higher, or -60°C or higher. Examples of such commercially available products include DIC Corporation's Boncoat® 5494EF (23°C), Boncoat® CE-8510 (-22°C), Boncoat® CE-1400 (-44°C), Boncoat® YG-651 (60°C), and Grandeur® PP-1000EF (130°C). In this specification, "glass transition temperature" refers to the value measured using a differential scanning calorimetry (DSC). Furthermore, the glass transition temperature is also indicated in parentheses for the above-mentioned commercially available products.

[0035] (B2) Higher fatty acids In this specification, "higher fatty acid" means a fatty acid (chain-like monocarboxylic acid) having 6 or more carbon atoms. In particular, from the viewpoint of highly suppressing the hydrolysis of aluminum nitride powder, those with 10 or more carbon atoms are preferred, and those with 15 or more carbon atoms are more preferred. Furthermore, considering the ease of combustion during calcination, those with 30 or fewer carbon atoms are preferred, 25 or fewer, and even more preferably 20 or fewer. Higher fatty acids are typically saturated fatty acids. Specific examples of higher fatty acids (and their carbon atoms) include caprylic acid (C8), capric acid (C10), lauric acid (C12), myristic acid (C14), palmitic acid (C16), stearic acid (C18), arachidic acid (C20), behenic acid (C22), montanic acid (C28), and mellitic acid (C30).

[0036] It is preferable that the higher fatty acids, like the water-soluble acrylic resin described above, do not decompose by heat treatment (e.g., heat treatment at 100-200°C) to dry the granulated powder. It is also preferable that the higher fatty acids burn off by debinding treatment (e.g., heat treatment at 200-600°C) or calcination treatment exceeding 600°C (e.g., heat treatment at 1000-2500°C). It is preferable that the decomposition temperature of the higher fatty acids is the heating temperature of the debinding treatment or calcination treatment described above, regardless of the calcination atmosphere.

[0037] The melting point (softening point) of higher fatty acids is typically higher than room temperature (e.g., 25±10°C, preferably 25±5°C), and from the viewpoint of improving the moldability and coherence of the granulated powder, it is preferable that it be generally 100°C or lower, for example, 80°C or lower, or 60°C or lower.

[0038] In the technology disclosed herein, when the amount of aluminum nitride powder is 100 parts by mass, the total proportion of additives is 5 to 20 parts by mass. This allows the additives to adhere evenly to the surface of the aluminum nitride powder, suppressing hydrolysis of the aluminum nitride powder and enabling the stable production of granulated powder that is less prone to collapse and has high coherence. From the viewpoint of exhibiting the effects of the technology disclosed herein at a higher level, the total proportion of additives is preferably 6 parts by mass or more, 8 parts by mass or more, or 10 parts by mass or more. Furthermore, from the viewpoint of improving the density and thermal conductivity of the ceramic sintered body or improving the moldability of the granulated powder, it may be 18 parts by mass or less, 16 parts by mass or less, or 15 parts by mass or less.

[0039] Furthermore, in the technology disclosed herein, when the total additive is considered as 100% by mass, the proportion of water-soluble acrylic resin is 50 to 98% by mass, and the proportion of higher fatty acids is 2 to 50% by mass. That is, the mass ratio of water-soluble acrylic resin to higher fatty acids constituting the additive is 98:2 to 50:50. Within the above mass ratio range, the proportions of both components can be appropriately changed depending on, for example, the properties (size, etc.) of the aluminum nitride powder or the application of the granulated powder. From the viewpoint of improving the moldability and integrity of the granulated powder, the proportion of water-soluble acrylic resin may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or even 90% by mass or more. From the viewpoint of suppressing the hydrolysis of aluminum nitride powder at a high level, the proportion of water-soluble acrylic resin may be 95% by mass or less. Also, from the viewpoint of suppressing the hydrolysis of aluminum nitride powder at a high level, the proportion of higher fatty acids may be 5% by mass or more. The proportion of higher fatty acids may be 40% by mass or less, 30% by mass or less, 20% by mass or less, or 10% by mass or less, from the viewpoint of improving the moldability and coherence of the granulated powder. Furthermore, from the viewpoint of exhibiting the effects of the technology disclosed herein at a higher level, the above mass ratio is preferably 95:5 to 90:10.

[0040] While not particularly limited, when the total granulated powder is considered as 100% by mass, the proportion of water-soluble acrylic resin is generally 1% by mass or more, typically 3% by mass or more, preferably 5% by mass or more, 7% by mass or more, or 10% by mass or more, and generally 30% by mass or less, typically 20% by mass or less, preferably 15% by mass or less, for example, 12% by mass or less. If the above proportion is above a predetermined value, the integrity and handling properties of the granulated powder can be improved. Also, if the above proportion is below a predetermined value, the aluminum nitride particles in the ceramic sintered body can come into contact with each other more easily, improving density and thermal conductivity.

[0041] While not particularly limited, when the total granulated powder is considered as 100% by mass, the proportion of higher fatty acids is generally 0.1% by mass or more, typically 0.2% by mass or more, preferably 0.25% by mass or more, and generally 10% by mass or less, typically 8% by mass or less, 5% by mass or less, preferably 2% by mass or less, for example, 1.5% by mass or less. If the above proportion is above a predetermined value, hydrolysis of the aluminum nitride powder can be suppressed more effectively. Also, if the above proportion is below a predetermined value, the aluminum nitride particles in the ceramic sintered body can come into contact with each other more easily, improving density and thermal conductivity.

[0042] (C) Other optional components The granulated powder may contain various optional components in addition to the above-mentioned components, namely (A) aluminum nitride powder and (B) additives, as long as the effects of the technology disclosed herein are not significantly impaired. Optional components may be selected from those conventionally known and commonly used in granulated powders, either individually or in combination of two or more as needed. Examples of optional components include (C1) other ceramic powders other than aluminum nitride powder, (C2) other resins other than water-soluble acrylic resins, plasticizers, dispersants, release agents, wetting agents, surfactants, defoamers, stabilizers, antioxidants, preservatives, colorants (pigments, dyes), pH adjusters, and various other additives.

[0043] (C1) Examples of ceramics that make up other ceramic powders include nitride-based ceramics such as boron nitride, silicon nitride, and gallium nitride; carbide-based ceramics such as silicon carbide; and oxide-based ceramics such as aluminum oxide, zinc oxide, magnesium oxide, beryllium oxide, and titanium oxide. When other ceramic powders are included, the proportion of aluminum nitride powder in the total ceramic powder (i.e., the sum of aluminum nitride powder as an essential component and other ceramic powders) should be approximately 50% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.

[0044] (C2) Other resins Other resins include, for example, water-soluble resins such as cellulose resins, polyvinyl alcohol resins, polyether resins, phenolic resins, and urethane resins. When other resins are included, the proportion of water-soluble acrylic resin in the total resin (i.e., the sum of water-soluble acrylic resin as an essential component and other resins) should be approximately 50% by mass or more, preferably 90% by mass or more, more preferably 95% by mass or more, and even more preferably 98% by mass or more.

[0045] [Method for manufacturing ceramic sintered bodies] Figure 2 is a flowchart of a manufacturing method according to one embodiment. As shown in Figure 2, the manufacturing method disclosed herein includes a raw material preparation step (step S1), a granulation step (step S2), a molding step (step S3), and a firing step (step S4) in this order. Furthermore, the manufacturing method disclosed herein may include other steps at any stage. Note that steps S1 and S2 can also be understood as a method for producing granulated powder. Also, steps S1 to S3 can be understood as a method for producing a green molded body.

[0046] In the raw material preparation step (step S1), the raw materials for the granulated powder are (A) aluminum nitride powder, (B) water-soluble acrylic resin and (B2) higher fatty acids as additives, and (C) other optional components as needed. The types, properties, and mixing ratios of these raw materials are as described above. It is preferable that the higher fatty acids be in the form of an emulsion suspended in an aqueous solvent.

[0047] In the granulation process (step S2), granulated powder is produced using the above raw materials. Any conventionally known granulation method may be used, and either wet granulation or dry granulation methods can be employed. Examples include rolling granulation, fluidized bed granulation, agitation granulation, compression granulation, extrusion granulation, crushing granulation, and spray drying (aerosol granulation). Among these, wet granulation is preferred because it can stably produce homogeneous granulated powder, and spray granulation is particularly preferred because it can easily produce roughly spherical particles. In an example of spray granulation, first, the prepared raw materials are dissolved or dispersed in a dispersion solvent to prepare a raw material slurry. The raw material slurry is prepared at a temperature of approximately 40°C or lower, typically at room temperature (for example, 25±10°C, preferably 25±5°C).

[0048] As shown in Figure 2, this embodiment includes a first mixing step (step S21), a second mixing step (step S22), and a spraying and drying step (step S23) in that order. The first mixing step (step S21) and the second mixing step (step S22) are examples of wet mixing steps in which the prepared raw materials are wet-mixed in a dispersion solvent.

[0049] In the first mixing step (step S21), a dispersion solvent is first prepared. From the viewpoint of reducing environmental impact and homogeneously dispersing the (B1) water-soluble acrylic resin, an aqueous solvent as described above is preferred, and water is more preferred. Next, the (B) additive prepared above, namely (B1) water-soluble acrylic resin and (B2) higher fatty acid, is added to the dispersion solvent and stirred and mixed. The stirring and mixing method is not particularly limited and can be carried out using conventionally known stirring and mixing devices, such as a ball mill, mixer, disper, kneader, etc. This prepares a preliminary mixture.

[0050] Next, in the second mixing step (step S22), (A) aluminum nitride powder is added to the premix prepared in the first mixing step and further stirred and mixed. This prepares the raw material slurry. The proportion of (A) aluminum nitride powder in the raw material slurry is preferably adjusted as appropriate depending on the granulation method. For example, when using a spray drying apparatus, the proportion of (A) aluminum nitride powder should be approximately 20 to 60% by mass when the total raw material slurry is considered to be 100% by mass.

[0051] Next, in the spraying and drying step (step S23), the raw material slurry is sprayed in droplet form using a spray dryer and dried. At this time, the size and mass of the granulated particles can be adjusted by adjusting the size of the sprayed droplets. The size of the sprayed droplets should be set, for example, so that the average particle size of the granulated powder falls within the above range. The heating temperature during drying is not particularly limited, as it may vary depending on, for example, the amount of solids in the raw material slurry and the melting temperature of the additives used, but it should be set to approximately 100°C or higher, 110°C or higher, preferably 120°C or higher, 150°C or higher, and generally 200°C or lower. In this way, granulated powder containing aluminum nitride particles and additives can be obtained. After the spraying and drying step (step S23), the obtained granulated powder may be subjected to a sizing treatment (crushing, sieving, etc.) as appropriate, for example, to adjust the average particle size and particle size distribution.

[0052] In the molding process (step S3), the granulated powder is molded into a green molded body of a desired shape and size. In this embodiment, by using the granulated powder, a green molded body that is less prone to collapse and has high coherence can be obtained. In this specification, "green molded body" refers to all unfired structures, regardless of whether they have undergone drying treatment. The method of molding the green molded body is not particularly limited, and conventionally known methods such as roll molding, press molding, tape molding, extrusion molding, and injection molding can be appropriately adopted depending on the desired size and shape, the intended use of the green molded body, etc. Examples of green molded bodies include sheet-like green sheets and columnar (prismatic, cylindrical) ones. The green molded body can be manufactured, for example, by pressure molding (preferably press molding). Press molding and the like can be carried out with conventionally known equipment (e.g., a uniaxial press).

[0053] In the firing process (step S4), the green molded body obtained above is fired. The firing conditions (e.g., firing temperature, firing time, heating rate, firing atmosphere, etc.) are not particularly limited and should be set appropriately according to the properties of the aluminum nitride powder. The firing temperature should be generally 600°C or higher, typically 1000°C or higher, 1500°C or higher, and generally 2500°C or lower, for example, 2000°C or lower. In this way, a ceramic sintered body can be obtained.

[0054] [Applications of ceramic sintered bodies] The granulated powder disclosed herein, as well as the green molded body and ceramic sintered body made using the granulated powder, can be used, for example, to form heat-dissipating substrates. For example, they can be used to create a heat-dissipating sheet that dissipates heat from a heat-generating component (e.g., a power device) by being interposed between the heat-generating component and the heat-dissipating component (heat-dissipating fins, heat sinks, heat-dissipating plates, etc.), or by replacing the heat-dissipating component. They can also be used to create a heat-dissipating device in combination with the heat-dissipating component.

[0055] The following describes some embodiments of the present invention, but the present invention is not intended to be limited to those shown in these embodiments.

[0056] <Example Test> In this test example, the relationship between the overhang length L in the granulated powder 10 and whether or not entanglement of the granulated powder 10 occurred was confirmed.

[0057] First, distilled water was placed in a plastic container as a dispersion solvent. Next, water-soluble acrylic resin (Boncoat CE-1400, manufactured by DIC Corporation) and higher fatty acid (Cerosol (trademark) 920, manufactured by Chukyo Oil & Fat Co., Ltd.) were added to the plastic container in the total proportions (parts by mass) shown in Table 1, and the mixture was stirred and mixed. The mixing ratio of water-soluble acrylic resin to higher fatty acid was 90:10 by weight. Next, aluminum nitride powder (AlN, manufactured by Combustion Synthesis Co., Ltd., irregular shape, average particle size: 5 μm) and needle-shaped particles made of aluminum nitride (also called whiskers, average diameter 10 mm, average length 50 mm) were added to the plastic container, and the mixture was thoroughly stirred and mixed in a pot mill to obtain the raw material slurries for Examples 1 to 6 and Comparative Example 4.

[0058] Next, the raw material slurry was spray-dried using a spray-drying apparatus to produce granulated powders for each example. The spraying conditions were set so that the average particle size of the granulated powder was approximately 50 μm. The heating and drying temperature was set to 180-200°C, and the amount of dispersed solvent contained in the granulated powder was approximately 0.5% by mass. This yielded the granulated powders for this test example.

[0059] Next, to check whether or not the granulated powder had become entangled with other particles, the prepared granulated powder was sieved. The sieve was sufficiently larger than the granulated powder but smaller than the thickness of the green sheet to be made using the granulated powder, for example, about 300 μm. By passing the powder through such a sieve once, any entangled particles will remain on the sieve, allowing them to be removed.

[0060] [Observation with an optical microscope] The prepared granulated powder was observed using an optical microscope. Specifically, optical microscope images were obtained for both the granulated powder that passed through the aforementioned sieve (i.e., the granulated powder that was not entangled) and the granulated powder that remained on the aforementioned sieve (i.e., the granulated powder that was entangled).

[0061] Then, using optical microscope images of the granulated powder that passed through the sieves and the granulated powder remaining on the sieves, the particle diameter and overhang length L of the granular portion 12 were measured for both the granulated powder without entanglement and the granulated powder with entanglement. Specifically, multiple samples, specifically 30 samples each, of granulated powder with particle diameters of 17 μm, 33 μm, 50 μm, 70 μm, 97 μm, and 133 μm were extracted from the images, and the overhang length L of each was measured on the image. Tables 1 and 2 show the maximum values ​​of the overhang length L for each particle diameter of the granular portion 12 for both the granulated powder without entanglement and the granulated powder with entanglement.

[0062] [Table 1]

[0063] [Table 2]

[0064] According to Table 1, for granulated powders that do not entangle, the overhang length L is 70 μm or less regardless of the particle size of the granular portion 12. On the other hand, according to Table 2, for granulated powders that do entangle, the overhang length L exceeds 70 μm regardless of the particle size of the granular portion 12.

[0065] The granulated powder 10 of this embodiment is made by including aluminum nitride powder and needle-shaped particles as raw materials, and the granulated powder 10 has needle-shaped portions 14, and the protruding length L of the needle-shaped portions 14 can be 70 μm or less.

[0066] Furthermore, since the granulated powder 10 in this embodiment is the precursor to the green sheet for the heat dissipation substrate, the needle-shaped particles in the granulated powder can improve the strength of the green sheet.

[0067] Furthermore, according to the granulated powder 10 of this embodiment, in addition to the raw materials, it contains a water-soluble acrylic resin and a higher fatty acid as additives, so even when aluminum nitride, which undergoes hydrolysis upon reaction with an aqueous solvent, is used as a raw material, granulated powder can be suitably produced.

[0068] Although the present invention has been described in detail above with reference to tables and drawings, the present invention can be implemented in other embodiments, and various modifications can be made without departing from its spirit.

[0069] In the above-described embodiment, the granulated powder 10 that does not entangle, that is, the granulated powder 10 that has passed through the sieve, was defined as granulated powder with an overhang length L of 70 μm or less. However, it is not limited to all granulated powder 10 having an overhang length L of 70 μm or less. According to the inventors' experiments, about 90% of the granulated powder 10 that passed through the sieve had an overhang length L of 70 μm or less, while the remaining 10% or so had an overhang length L exceeding 70 μm. Thus, even if a certain proportion of granulated powder has an overhang length L exceeding 70 μm, entanglement between the granulated powders can be suppressed.

[0070] In the above-described embodiment, the granulated powder 10 was composed of one granular portion 12 and one needle-shaped portion 14 penetrating it, but the configuration is not limited to this. Specifically, for example, it may be composed of one granular portion 12 and multiple needle-shaped portions 14 penetrating it. In this case, the protruding length L is the length of the longest protruding of the multiple needle-shaped portions 14.

[0071] In the above-described embodiment, the needle-shaped particles were crystals of aluminum nitride, but the embodiment is not limited to this. For example, the needle-shaped particles may be composed of other materials. For example, they may be crystals of nitride-based ceramics such as boron nitride, silicon nitride, and gallium nitride, carbide-based ceramics such as silicon carbide, or oxide-based ceramics such as aluminum oxide, zinc oxide, magnesium oxide, beryllium oxide, and titanium oxide, as exemplified as ceramics constituting the (C1) other ceramic powder described above.

[0072] In the above-described embodiment, the granulated powder was passed through a sieve once to confirm whether or not entanglement had occurred. However, the method is not limited to this, and powder that has passed through the sieve multiple times may be considered as not being entangled.

[0073] It should be noted that the above is merely one embodiment, and although other examples are not provided, the present invention can be implemented in various modified and improved forms based on the knowledge of those skilled in the art, without departing from its spirit. [Explanation of Symbols]

[0074] 10 Granulated powder 12 Granular part 14 Needle-shaped part L Overhang length

Claims

1. A granulated powder made containing aluminum nitride powder and needle-shaped particles as raw materials, The granulated powder has needle-like protrusions, The length of the aforementioned needle-like projections shall be 70 μm or less. A granulated powder characterized by the following.

2. It is the front casing for the green sheet used for the heat dissipation substrate. The granulated powder according to claim 1, characterized by the above.

3. In addition to the above raw materials, the additives include a water-soluble acrylic resin and a higher fatty acid. The granulated powder according to claim 1, characterized by the above.

Citation Information

Patent Citations

  • Granulated powder containing aluminum nitride powder and use thereof, and method for producing granulated powder

    JP2023148541A